2011
DOI: 10.1021/bm200375x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning Micellar Core-Forming Block of Poly(ethylene glycol)-block-poly(ε-caprolactone) Amphiphilic Copolymers Based on Chemical Modification for the Solubilization and Delivery of Doxorubicin

Abstract: This study aimed to optimize poly(ethylene glycol)-b-poly(ε-caprolactone) (PEG-b-PCL)-based amphiphilic block copolymers for achieving a better micellar drug delivery system (DDS) with improved solubilization and delivery of doxorubicin (DOX). First, the Flory-Huggins interaction parameters between DOX and the core-forming segments [i.e., poly(ε-caprolactone) (PCL) and poly[(ε-caprolactone-co-γ-(carbamic acid benzyl ester)-ε-caprolactone] (P(CL-co-CABCL))] was calculated to assess the drug-polymer compatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 50 publications
9
96
1
2
Order By: Relevance
“…51 These two melting events suggest the existence of two distinct crystalline domains in the miktoarm polymer. 30 CoQ10/PEG2-PCL3.8-TPPBr physical mixture shows the same characteristic melting peaks for both CoQ10 and PEG2-PCL3.8-TPPBr copolymer ( Figure 4B). In contrast, the DSC thermogram of the lyophilized CoQ10/PEG2-PCL3.8-TPPBr micelle shows a bimodal endothermic peak at 45.40 and 48.31°C corresponding, respectively, to the melting of PEG and CoQ10 ( Figure 4B).…”
Section: ■ Results and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…51 These two melting events suggest the existence of two distinct crystalline domains in the miktoarm polymer. 30 CoQ10/PEG2-PCL3.8-TPPBr physical mixture shows the same characteristic melting peaks for both CoQ10 and PEG2-PCL3.8-TPPBr copolymer ( Figure 4B). In contrast, the DSC thermogram of the lyophilized CoQ10/PEG2-PCL3.8-TPPBr micelle shows a bimodal endothermic peak at 45.40 and 48.31°C corresponding, respectively, to the melting of PEG and CoQ10 ( Figure 4B).…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…Several recent studies have shown that polymer−drug compatibility is a key factor in determining the performance of polymeric micelle as drug delivery systems where high compatibility results in higher drug solubility, loading capacity, and controlled drug release. 30,31,45,46 To explain the exceptionally high CoQ10 loading into PEG2-PCL3.8-TPPBr micelles, we used the Flory−Huggins interaction parameter (χ sm ) to estimate the CoQ10-PCL compatibility, because it has been shown to be a good indicator of polymer−drug compatibility. 31,47 The Hansen partial solubility parameters for CoQ10, nimodipine, and PCL were obtained based on the group contribution method using the Molecular Modeling Pro software (Table 1, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the case of the nonpolar components or components without specific interactions (e.g., hydrogen bonding), and if the excess entropy and excess volume can be ignored, v ij can be obtained from the solubility parameters 39,40 …”
Section: 17mentioning
confidence: 99%
“…[ 27 ] The introduction of a benzyl ester group to poly(ethylene glycol)-blockpoly( ε -caprolactone) was also achieved, which showed a delayed release of DOX as a result of π -π stacking. [ 28 ] Herein, we report a new synthesis of well-defi ned poly( N -(2-hydroxypropyl)methacrylamide)-block -poly(benzyl methacrylate) (PHPMA-b -PBnMA) using the RAFT polymerization without post-polymerization modifi cation. The terminal dithiobenzoate group of the polymer was converted into the corresponding carboxylic acid by a one pot reaction with NaBH 4 /acrylic acid, which readily underwent a conjugation reaction with aminated-folic acid (FA-NH 2 ).…”
Section: Preparation Of Fa Conjugated Micellesmentioning
confidence: 99%